Question
upstudy study bank question image url

Given that \( f(x)=x^{2}-4 x \) and \( g(x)=x+4 \), find (a) \( (f+g)(x)= \) (b) \( (f-g)(x)= \) प (c) \( (f g)(x)= \) (d) \( \left(\frac{f}{g}\right)(x)= \) Question Help:

Ask by O'Quinn Graham. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

(a) \( (f+g)(x) = x^2 - 3x + 4 \) (b) \( (f-g)(x) = x^2 - 5x - 4 \) (c) \( (fg)(x) = x^3 - 16x \) (d) \( \left(\frac{f}{g}\right)(x) = \frac{x(x - 4)}{x + 4} \)

Solution

To solve the problem, we will find the sum, difference, product, and quotient of the functions \( f(x) \) and \( g(x) \). Given: - \( f(x) = x^2 - 4x \) - \( g(x) = x + 4 \) Let's solve each part step by step. ### (a) \( (f+g)(x) \) The sum of the functions \( f \) and \( g \) is given by: \[ (f+g)(x) = f(x) + g(x) \] Substituting the expressions for \( f(x) \) and \( g(x) \): \[ (f+g)(x) = (x^2 - 4x) + (x + 4) \] Now, combine like terms: \[ (f+g)(x) = x^2 - 4x + x + 4 = x^2 - 3x + 4 \] ### (b) \( (f-g)(x) \) The difference of the functions \( f \) and \( g \) is given by: \[ (f-g)(x) = f(x) - g(x) \] Substituting the expressions for \( f(x) \) and \( g(x) \): \[ (f-g)(x) = (x^2 - 4x) - (x + 4) \] Now, distribute the negative sign and combine like terms: \[ (f-g)(x) = x^2 - 4x - x - 4 = x^2 - 5x - 4 \] ### (c) \( (fg)(x) \) The product of the functions \( f \) and \( g \) is given by: \[ (fg)(x) = f(x) \cdot g(x) \] Substituting the expressions for \( f(x) \) and \( g(x) \): \[ (fg)(x) = (x^2 - 4x)(x + 4) \] Now, we will expand this expression: \[ (fg)(x) = x^2 \cdot (x + 4) - 4x \cdot (x + 4) \] \[ = x^3 + 4x^2 - 4x^2 - 16x \] \[ = x^3 - 16x \] ### (d) \( \left(\frac{f}{g}\right)(x) \) The quotient of the functions \( f \) and \( g \) is given by: \[ \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} \] Substituting the expressions for \( f(x) \) and \( g(x) \): \[ \left(\frac{f}{g}\right)(x) = \frac{x^2 - 4x}{x + 4} \] This expression can be simplified if possible. We can factor the numerator: \[ = \frac{x(x - 4)}{x + 4} \] Now, we have all the required expressions: ### Final Answers: (a) \( (f+g)(x) = x^2 - 3x + 4 \) (b) \( (f-g)(x) = x^2 - 5x - 4 \) (c) \( (fg)(x) = x^3 - 16x \) (d) \( \left(\frac{f}{g}\right)(x) = \frac{x(x - 4)}{x + 4} \)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To solve the given problems, let's start by calculating each of the required operations: Given: - \( f(x) = x^2 - 4x \) - \( g(x) = x + 4 \) (a) For \( (f+g)(x) \): \[ (f+g)(x) = f(x) + g(x) = (x^2 - 4x) + (x + 4) = x^2 - 3x + 4 \] (b) For \( (f-g)(x) \): \[ (f-g)(x) = f(x) - g(x) = (x^2 - 4x) - (x + 4) = x^2 - 5x - 4 \] (c) For \( (fg)(x) \): \[ (fg)(x) = f(x) \cdot g(x) = (x^2 - 4x)(x + 4) = x^3 + 4x^2 - 4x^2 - 16x = x^3 - 16x \] (d) For \( \left(\frac{f}{g}\right)(x) \): \[ \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{x^2 - 4x}{x + 4} \] This can be simplified: \[ = \frac{x(x-4)}{x+4} \] It’s important to note that this expression is undefined when \( g(x) = 0 \), i.e., when \( x = -4 \). So the final answers are: (a) \( (f+g)(x) = x^2 - 3x + 4 \) (b) \( (f-g)(x) = x^2 - 5x - 4 \) (c) \( (fg)(x) = x^3 - 16x \) (d) \( \left(\frac{f}{g}\right)(x) = \frac{x(x-4)}{x+4} \) (undefined at \( x = -4 \))

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy